Analisis Efisiensi Saluran Pemasaran Jambu Mete di Desa Rakadua, Kecamatan Poleang Barat, Bombana - Nurfadila Nurfadila; Campina Illa Prihantini; Erni Erni; Samaria Samaria; Erwin Erwin (Fakultas Pertanian, Universitas Timor, 2021)
The main problem in this study is that the cashews sold by farmers are still in the form of logs and not in processed form (processed cashew kernels). The purpose of this study was to analyze the trading system and marketing margins of cashew in Rakadua Village, Bombana Regency. The research method used in this study is a qualitative research with a descriptive approach which aims to provide an overview of the research problem. Based on the results of the study, the trade system used by cashew farmers in Rakadua Village, Poleang Barat District, Bombana Regency has used these four trading channels. Marketing channel I is the simplest trading system pattern, while marketing channel II, III, and IV are the most complex channels, namely by passing the most intermediaries. The results of this study may become the basis in the process of formulating policies issued by the government in order to improve the quality of cashews, especially for farmers.